2008
DOI: 10.1016/j.surg.2008.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Acute, regional inflammatory response after traumatic brain injury: Implications for cellular therapy

Abstract: While cellular therapy has shown promise in the management of traumatic brain injury (TBI), microenvironment interactions between the intracerebral milieu and therapeutic stem cells are poorly understood. We sought to characterize the acute, regional inflammatory response after TBI. Rats underwent a controlled cortical impact (CCI) injury or sham injury, were sacrificed at 6, 12, 24, 48, and 72 hours, and intracerebral fluid (IF) was isolated from the direct injury, penumbral, ipsilateral frontal, contralatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 28 publications
5
81
1
Order By: Relevance
“…We found a robust reduction in microglial activation 48 h post-CCI, the peak of microgliosis in our CCI model and other experimental TBI models (Harting et al, 2008;Ziebell and Morganti-Kossmann, 2010). To our knowledge these are the first data to show an anti-inflammatory effect of LLLT in the immune response to TBI.…”
Section: Khuman Et Alsupporting
confidence: 68%
“…We found a robust reduction in microglial activation 48 h post-CCI, the peak of microgliosis in our CCI model and other experimental TBI models (Harting et al, 2008;Ziebell and Morganti-Kossmann, 2010). To our knowledge these are the first data to show an anti-inflammatory effect of LLLT in the immune response to TBI.…”
Section: Khuman Et Alsupporting
confidence: 68%
“…Although a hyperacute cell transplantation (Ͻ24 h after injury) strategy has shown cell survival and behavioral benefit [5-7, 16, 24], recent work is revealing that the acute, central nervous system proinflammatory microenvironment is suboptimal for survival of grafted cells [25]. We chose the 7-d time point because the optimal time window may be after the acute inflammatory cascade, including cytokine release, macrophage/microglia infiltration, and edema (which all appear to resolve around d 5-6 after injury), yet prior to glial scar formation (which is observed to begin forming around d 10 -14) [25,26].…”
Section: Figmentioning
confidence: 99%
“…In healthy patients, the plasma level of TNF-α is generally smaller than 1 pg/mL, but its concentration can be abnormally high in the presence of atherosclerosis, [9][10][11][12] during tumorigenesis and tumor growth, 13 in patients with rheumatoid arthritis, 14 in women undergoing pre-eclamptic pregnancies, 15 and in obese individuals. 16 In incidences of acute trauma, elevated circulating levels of TNF-α have also been reported, including, but not limited to, traumatic brain injury 17 and hemorrhagic shock. 18,19 Also, others have reported that soluble forms of membrane receptors (TNFR) rather than TNF-α are initially released following trauma (based on serum levels one hour after arrival at a trauma center) and may serve as an indirect indicator that TNF-α associates with trauma.…”
Section: Introductionmentioning
confidence: 99%